Computational Studies on the Potency and Selectivity of PUGNAc Derivatives Against GH3, GH20, and GH84 β-N-acetyl-D-hexosaminidases - Dong, Lili; Shen, Shengqiang; Xu, Yefei; Wang, Leng; Feng, Ruirui; Zhang, Jianjun; Lu, Huizhe (Frontiers in Chemistry, 2019)
β-N-acetyl-D-hexosaminidases have attracted significant attention due to their crucial role in diverse physiological functions including antibacterial synergists, pathogen defense, virus infection, lysosomal storage, and protein glycosylation. In particular, the GH3 β-N-acetyl-D-hexosaminidase of V. cholerae (VcNagZ), human GH20 β-N-acetyl-D-hexosaminidase B (HsHexB), and human GH84 β-N-acetyl-D-hexosaminidase (hOGA) are three important representative glycosidases. These have been found to be implicated in β-lactam resistance (VcNagZ), lysosomal storage disorders (HsHexB) and Alzheimer’s disease (hOGA). Considering the profound effects of these three enzymes, many small molecule inhibitors with good potency and selectivity have been reported to regulate the corresponding physiological functions. In this paper, the best-known inhibitors PUGNAc and two of its derivatives (N-valeryl-PUGNAc and EtBuPUG) were selected as model compounds and docked into the active pockets of VcNagZ, HsHexB, and hOGA, respectively. Subsequently, molecular dynamics simulations of the nine systems were performed to systematically compare their binding modes from active pocket architecture and individual interactions. Furthermore, the binding free energy and free energy decomposition are calculated using the MM/GBSA methods to predict the binding affinities of enzyme-inhibitor systems and to quantitatively analyze the contribution of each residue. The results show that PUGNAc is deeply-buried in the active pockets of all three enzymes, which indicates its potency (but not selectivity) against VcNagZ, HsHexB, and hOGA. However, EtBuPUG, bearing branched 2-isobutamido, adopted strained conformations and was only located in the active pocket of VcNagZ. It has completely moved out of the pocket of HsHexB and lacks interactions with HsHexB. This indicates why the selectivity of EtBuPUG to VcNagZ/HsHexB is the largest, reaching 968-fold. In addition, the contributions of the catalytic residue Asp253 (VcNagZ), Asp254 (VcNagZ), Asp175 (hOGA), and Asp354 (HsHexB) are important to distinguish the activity and selectivity of these inhibitors. The results of this study provide a helpful structural guideline to promote the development of novel and selective inhibitors against specific β-N-acetyl-D-hexosaminidases.